The Prevalence of Temporomandibular Disorder in Iran: A Literature Review - Sajad Ghorbanizadeh; Kamran Azadbakht; Hamid Badrian; Nakisa Torabnia (Journal of Dentistry)
Statement of the Problem: Temporomandibular joint disorder (TMD) will appear if there is a problem with the temporomandibular joint, bones, related muscles, or ligaments. This complication causes severe joint pain near the ears, head, neck, and jaws. TMD has been reported to affect 40 to 70% of adults.Purpose: Based on previous studies, the present review aimed to determine the prevalence of TMD among the Iranian population.Materials and Method: This review and meta-analysis was performed according to the PRISMA guidelines. All relevant studies published during 2000-2023 were retrieved by a systematic search in available international databases, including Web of Science, Science Direct, Scopus, PubMed, and Google Scholar, and domestic Persian databases, including SID, Magiran, and Iran Medex. Finally, 22 completely related studies were selected to investigate the main objective. The Comprehensive Meta-analysis (CMA) software was used for data analysis in this systematic review.Results: Initially, 212 articles were retrieved, of which 116 were duplicate studies. Further, 39 studies were excluded after evaluation of the title and abstract, and 35 studies were excluded after considering the inclusion and exclusion criteria. Finally, 22 articles were included in the meta-analysis. The pooled prevalence of TMD in Iran was 0.56 (0.44-0.68).Conclusion: In general, the prevalence of TMD in the Iranian population is relatively high. Therefore, it is necessary to develop strategies to educate people, especially those at risk. Furthermore, due to the presence of TMD in children and students in some parts of the country, it is necessary to perform essential examinations in preschools to prevent the development of this disorder in later life.